Management priorities and management ethics - Longenecker, Justin G. (Journal of business ethics, 1985)
The management process affects the level of ethical performance in organizational life. As one part of this process, managers establish priorities which give direction to an organization. In business firms, management typically stresses the attainment of profits and other related economic and technical factors. Since little explicit recognition is given to ethics, the resulting climate makes it easy to ignore ethical factors. Changing this situation by making ethics a significant part of the corporate culture is difficult and requires a combination of management communication and management example. However, managers who choose to emphasize ethics and who skillfully articulate their importance can improve the integration of ethics into the day-to-day operating decisions of the firm.